Beatles vs. Stones - McMillian, John Campbell (Simon & Schuster, 2013)
"With the sophistication of a historian, the storytelling skills of a journalist, and the passion of a fan, John McMillian explores the multifaceted relationship between the two greatest bands of our time. In the 1960s the two biggest bands in the world the lovable Beatles and the bad-boy Rolling Stones waged an epic battle. The Beatles want to hold your hand, wrote Tom Wolfe, but the Stones want to burn down your town. Both groups liked to maintain that they weren t really rivals that was just a media myth, they politely said but on both sides of the Atlantic, they plainly competed for commercial success and aesthetic credibility. In Beatles vs. Stones, John McMillian gets to the truth behind the ultimate rock n roll debate. McMillian reveals how music managers helped to construct the Beatles-Stones rivalry as they set out to engineer moneymaking empires. He explores how the Beatles were marketed as cute and amiable, when in fact they came from hardscrabble backgrounds in Liverpool. By contrast, the Stones were cast as an edgy, dangerous group, even though they mostly hailed from the London suburbs. Although the Beatles always sold more records than the Stones, the Stones seemed to win greater credibility with the right types of fans: discerning bohemians, as opposed to hysterical teenyboppers. Later, the Beatles embraced Flower Power, while the Stones briefly aligned themselves with New Left militance. Ever since, writers and historians have associated the Beatles with the gauzy idealism of the good sixties and portrayed the Stones as representatives of the dangerous and nihilistic bad sixties. Beatles vs. Stones explodes that split. In a lively narrative that whisks readers from Liverpool to London to New York City and to various recording studios, nightclubs, concerts, courtrooms, and protest rallies in between McMillian also delves into the personal relationships between the two groups. In one chapter we see Lennon and McCartney huddle up in a rehearsal space and show the Stones how to write their own material; in another we eavesdrop on Jagger and Richards as they watch the Beatles play Shea Stadium from the visitors dugout. McMillian also shows us how the two groups feuded about which act would headline a legendary Poll Winners concert and the pernicious effect that the American businessman Allen Klein had on both bands. Based on exhaustive research in primary sources, including overlooked teen magazines and underground newspapers, Beatles vs. Stones tells a vital story of the 1960s through the lens of music s greatest rivalry. Spirited, insightful, and gracefully written, this is the definitive account of the friendship and rivalry between the Beatles and the Rolling Stones."